Tinjauan Kelengkapan Pengisian Lembar Ringkasan Pulang Resume Pasien Rawat Inap Di Rs Permata Cibubur - Kusnadi, Fery; Setiatin, Sali (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Quality medical documentation is the foundation of the healthcare system with a direct impact on continuity of care and clinical accountability. The medical resume as an integral component of the medical record serves as a holistic synthesis of therapeutic modalities during hospitalization. This investigation analyzes the completeness of the completion of medical resume documentation through a four-dimensional evaluation: identification modules, clinical reportage segments, authentication elements, and documentation aspects according to standards. This methodology applies a descriptive quantitative paradigm with a cross-sectional survey design on 60 samples of inpatient medical resume documents at Permata Cibubur Hospital during June 2025 using Simple Random Sampling. The research instrument consists of a structured checklist for systematic evaluation through direct observation of the medical resume form. The results of the analysis showed variations in the level of completeness: identification components 95% (5% deficiencies), critical report segments 88.87% (11.13% incomplete), authentication 92.22% (7.78% incompleteness), and proper documentation 93.4% (6.6% incompleteness). The findings show that although the majority of components meet good documentation standards, significant gaps still exist that require systematic optimization. Strategic implications for institutional management include the implementation of a continuous monitoring system and a structured training program for medical personnel to achieve 100% standards in accordance with the Regulation of the Minister of Health Number 24 of 2022.